Leadership and the rule of law in conflict and post-conflict societies: A leadership approach through the sustainable development goals. Issue 3 (12th August 2019) - Jean, Stéphane
Abstract : Purpose: The purpose of this paper is to explore the leadership dimensions in developing the rule of law. The paper considers the perspective from the United Nations, with the leadership tension is primarily seen from the prism of the rule of law. Design/methodology/approach: This paper explores the leadership challenges in specific recent case studies. Findings: The paper concludes that the most difficult challenge is a culture shift toward respect for the rule of law is required. The paper notes the importance of political leadership in developing consensus. Originality/value: The challenge is that the implementation of rule of law reform is primarily a political endeavor that affects the balance of powers within the State. This need for leaders to develop the space for institutions advancing the rule of law is most certainly the case in, and exacerbated by, conflict and post-conflict situations.